Insufficient radiofrequency ablation promotes proliferation of residual hepatocellular carcinoma via autophagy. (1st May 2018) - Zhao, Zizhuo; Wu, Jiayi; Liu, Xiaodi; Liang, Ming; Zhou, Xinchuan; Ouyang, Shi; Yao, Jiyi; Wang, Jinquan; Luo, Baoming
Abstract: Radiofrequency ablation (RFA) is considered to be a potentially curative therapy for hepatocellular carcinoma (HCC). However, insufficient RFA (IRFA) can promote rapid progression of the residual tumor. The mechanisms underlying IRFA-induced tumor promotion remain poorly understood. In the present study, we have established a subcutaneous xenograft mouse model and monitored the location and extent of IRFA by dual monitoring with ultrasonography and a thermal imager. For the first time, we provide evidence of the activation of autophagic pathways in mice exposed to IRFA. We show that autophagy plays an important role in relapse and proliferation after IRFA and that hydroxychloroquine (HCQ) can suppress these effects. Our findings indicate that autophagy is involved in experimental IRFA and that inhibition of autophagy may be a novel approach in the treatment of local recurrences of HCC after IRFA in the clinic. Highlights: A mouse model of insufficient radiofrequency ablation (IRFA) was established. Evidence of the activation of autophagic pathways in mice after IRFA was confirmed. Hydroxychloroquine (HCQ) can suppress relapse and proliferation after IRFA.